Introduzione alla Statistica Computazionale con R - Bertaccini, Bruno (Strumenti per la didattica e la ricerca, 2018)
Nowadays, the information transfer speed (on the web, but not only) requires the predisposition of ever more adequate analysis tools for working with data and increasingly faster algorithms, in order to allow the so-called decision maker to make decision based on information which can become obsolete very quickly with time. In the current situation, analysing this information in order to simulate complex decision-making scenarios could prove fundamental to secure an advantage over competitors. This text introduces the true art of Statistical Computing. In other words, it illustrates how computer programming skills in the development of algorithms can be used within Statistics for the virtual simulation and replication of realities and experiments of varying complexity. In order to do so, it uses the excellent development environment "R".